The Pulse Wave Velocity is Linearly Correlated with Resting Systolic and Diastolic Blood Pressure in Hypertensive Patients - Elka, Kana; Rotty, Monique; Winata, Johan; Pangemanan, Janry; Panda, A. Lucia (The Indonesian Heart Association, 2018)
Introduction: Aortic stiffness is an independent predictor for cardiovascular event. If arteries lose their natural elasticity, systolic blood pressure become higher and diastolic blood pressure become lower. Method of evaluating arterial stiffness is aortic pulse wave velocity (PWV). Therefore, PWV has a potential application for screening vascular damage in large population.2 Recent reports have shown that PWV obtained by noninvasive automatic devices (i.e. tonometry, cuff pressure) is not only a marker of vascular damages, but also a prognostic predictor in patients with hypertension.3 The aim of this study is to investigate the correlation between PWV and systolic and diastolic blood pressure. Methods : Male hypertensive patients, aged 40-60 years old who underwent Doppler Vascular were included in this study. The measurement of carotid-femoral PWV is made by dividing the distance (from the carotid point to the femoral point) by the so-called transit time (the time of travel of the foot of the wave over the distance). Hence, PWV = D (meters)/Dt (seconds). The correlation between PWV and systolic and diastolic blood pressure were analysed using linear regression test. Results : A total 40 patients were included in this study. Those were significant correlation between PWV and systolic (R=0.473, p=0.002) and diastolic (R=0.454, p=0.003) blood pressure. Conclusion : increasing PWV is linearly associated with systolic and diastolic blood pressure.   Abstrak Pendahuluan: Kekakuan aorta adalah prediktor independen untuk kejadian kardiovaskular. Jika elastisitas alami arteri hilang, tekanan darah sistolik menjadi lebih tinggi dan tekanan darah diastolik menjadi lebih rendah. Metode evaluasi kekakuan arteri adalah kecepatan gelombang pulsasi (pulse wave velocity/PWV). Oleh karena itu, PWV dapat diterapkan untuk skrining kerusakan vaskular pada populasi besar.2 Laporan terbaru menunjukkan bahwa PWV yang diperoleh dengan perangkat otomatis non-invasif (yaitu tonometri, tekanan manset) tidak hanya merupakan penanda kerusakan vaskular, tetapi juga prediktor prognostik pada pasien dengan hipertensi.3 Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara PWV dan tekanan darah sistolik dan diastolik. Metode: Pasien pria dengan hipertensi, berusia 40-60 tahun yang menjalani Doppler Vascular dimasukkan dalam penelitian ini. Pengukuran PWV karotid-femoralis dilakukan dengan membagi jarak (dari titik karotid ke titik femoral) dengan waktu transit. Oleh karena itu, PWV = D (meter) / Dt (detik). Korelasi antara tekanan darah PWV dan sistolik dan diastolik dianalisis dengan menggunakan uji regresi linier. Hasil: Sebanyak 40 pasien dimasukkan dalam penelitian ini. Itu adalah korelasi yang signifikan antara tekanan darah PWV dan sistolik (R = 0,473, p = 0,002) dan diastolik (R = 0,454, p = 0,003). Kesimpulan: Peningkatan PWV berhubungan linear dengan tekanan darah sistolik dan diastolik.